2005
DOI: 10.28945/275
|View full text |Cite
|
Sign up to set email alerts
|

The Insiders’ Perspectives: A Focus Group Study on Gender Issues in a Computer-Supported Collaborative Learning Environment

Abstract: Executive SummaryThere is little doubt that the advent of collaborative technologies in recent years has brought some significant changes in the way students learn, communicate, and interact with one another. In recent years, this emergence has sparked increased interest for research into the role and impact of instructional technologies on group learning. Despite the widespread use of different instructional technologies to support teaching and learning in today's classroom, our understanding of these technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…On hypothesis two, the finding is in line with the findings of Mitra, Lenzmeier, Avon, Qu and Hazen (2000) and Huynh, Lee and Schuldt (2005) based on their review on computers and the effect of gender on use of Computer Assisted instructional package of Anulobi (2009) and Yusuf and Afolabi (2010). The findings contradict the findings of Achuonye and Olele (2009) and Ofili (2015) which stressed the indicated male and female supremacy in computer usage and Ease of Use of PowerPoint.…”
Section: Discussion Of the Findingssupporting
confidence: 83%
“…On hypothesis two, the finding is in line with the findings of Mitra, Lenzmeier, Avon, Qu and Hazen (2000) and Huynh, Lee and Schuldt (2005) based on their review on computers and the effect of gender on use of Computer Assisted instructional package of Anulobi (2009) and Yusuf and Afolabi (2010). The findings contradict the findings of Achuonye and Olele (2009) and Ofili (2015) which stressed the indicated male and female supremacy in computer usage and Ease of Use of PowerPoint.…”
Section: Discussion Of the Findingssupporting
confidence: 83%
“…They found that girls with no experience made significant gains in learning in a short period of time. Huynh et al (2005) and Ying et al's (2021) study had different results in this regard. When researching the motivation of mixed-gender CSCL pairs, they found women to report significantly higher stress levels, lower levels of perceived competence, and less perceived choice than men.…”
Section: Empirical Findingsmentioning
confidence: 88%
“…Others find that the scope of unconscious gender bias in STEM education became clear when observing that higher female participation did not automatically reduce differential treatment and stereotyped perception of women in CSCL learning experiences (Rambe 2017;Ying et al 2021). They further find that a deeply rooted gender bias still exists in the classroom today, and carries over to technology-supported learning environments in CSCL (Huynh et al 2005;Cintron et al 2019;Richterich 2019).…”
Section: Cscl and Gender Equalitymentioning
confidence: 99%
“…This finding is in agreement with the finding of: Spotts et al (1997) Achuonye and Olele (2009) who noted that there is significant difference between males and females pupils exposed to CAI. Huynh et., al (2005) found that there is no statistical significant validating difference in the pattern of online interaction between males and females students. Also Yusuf and Afolabi (2010) Bello cited in Achuonye (2011) noted that gender has no influence on performance of males and females pupils exposed to CAI .These were however disapproved by the result of this study which showed that the male gender achieved better scores with CAIPNL than the female gender.…”
Section: Discussionmentioning
confidence: 99%